Attitudes of U.N.R.W.A. School Pprincipals Towards Physical Education Program - Mohd. Khamis Abu Nimreh (My University, 2002)
The purpose of the study was to determine the attitudes of U.N.R.W.A school principals towards the physical education program. The sample of the study comprised (90) male and female school principals. The researcher used (33) items questionnaire to determine the principals attitudes after testing its validity and reliability. The questionnaire contains (4) domains: Financial support and activities, Planning, Leadership, and Evaluation. The results of the study were as follows: 1. U.N.R.W.A. school principals showed positive attitudes towards the physical education program. 2. There were no significant differences between male and female school principals attitudes in all domains and total score of the questionnaire. 3. There were significant differences due to the year of experience in financial support and activities sub-scale and in Planning sub-scale of the questionnaire. 4. No significant differences existed due to academic qualifications in all sub-scales of the questionnaire. The researcher recommended the following: 1. Reinforcement of the positive attitudes of school principals toward P.E. program. 2. Organizing and conducting seminars on the supervision of P.E. program in general to school principals to improve their skills in this area. 3. Conducting research studies dealing with the students attitudes towards physical education – program.